2017
DOI: 10.1108/ijqrm-09-2015-0143
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modelling of a wind electric generating power plant

Abstract: Purpose The purpose of this paper is to analyse the performance of a wind electric generating power plant through the study of reliability measures. The enhancement of the performance of the wind power plant using various approaches is also an objective of this paper. Design/methodology/approach This paper describes two models of a wind electric generating power plant using the Markov process and supplementary variable technique and solved with the help of Laplace transformation. The first model has been ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The proposed framework discriminates between the use of statistical distributions to represent the time to failure (i.e., renewal approach) and the use of stochastic point process (repairable system approach). It is also observed that several papers used specific reliability distributions for failure and repair data analysis (Goyal and Ram, 2017;Ghavijorbozeh and Hamadani, 2017;Haldar, 2015;Mohammadi et al, 2015;Tsarouhas, 2015). Saleh (2009, 2010) conducted a nonparametric analysis of satellite reliability for 1584 Earth-orbiting satellites launched between January 1990 and October 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed framework discriminates between the use of statistical distributions to represent the time to failure (i.e., renewal approach) and the use of stochastic point process (repairable system approach). It is also observed that several papers used specific reliability distributions for failure and repair data analysis (Goyal and Ram, 2017;Ghavijorbozeh and Hamadani, 2017;Haldar, 2015;Mohammadi et al, 2015;Tsarouhas, 2015). Saleh (2009, 2010) conducted a nonparametric analysis of satellite reliability for 1584 Earth-orbiting satellites launched between January 1990 and October 2008.…”
Section: Literature Reviewmentioning
confidence: 99%